2017
DOI: 10.1108/jmd-06-2016-0093
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting universities’ ability to foster students’ entrepreneurial behaviour

Abstract: Purpose The purpose of this paper is to empirically investigate behavioural and contextual factors affecting entrepreneurial universities’ ability to influence student entrepreneurship and entrepreneurial intention. Design/methodology/approach Structural equation modelling was used to assess both micro and macro factors impacting on students’ entrepreneurial attitude and intention on a sample of 272 students of the Master of Business Administration at the University of Florence (Italy). Findings The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 55 publications
5
39
2
2
Order By: Relevance
“…Although the decision to start a business is determined by other factors, university education plays an important role in this process. This is consistent with the findings of Zollo et al, (2017) and Shirokova et al, (2016), which show that the university environment has a significant impact on students in their business attitude and intentions (Bergmann et al, 2018(Bergmann et al, , 2016Hahn et al, 2017;Trivedi, 2016). In addition, Walter et al (2013) point out that during the course of higher education, the four factors of the organization of study that play a key role in the future business of students are: entrepreneurial education, support programs for entrepreneurship, interconnection with industry, and research orientation.…”
Section: Empirical Results and Discussionsupporting
confidence: 86%
“…Although the decision to start a business is determined by other factors, university education plays an important role in this process. This is consistent with the findings of Zollo et al, (2017) and Shirokova et al, (2016), which show that the university environment has a significant impact on students in their business attitude and intentions (Bergmann et al, 2018(Bergmann et al, , 2016Hahn et al, 2017;Trivedi, 2016). In addition, Walter et al (2013) point out that during the course of higher education, the four factors of the organization of study that play a key role in the future business of students are: entrepreneurial education, support programs for entrepreneurship, interconnection with industry, and research orientation.…”
Section: Empirical Results and Discussionsupporting
confidence: 86%
“…Zhang et al (2014) found positive association between entrepreneurship education and entrepreneurial intention among Chinese students. Zollo (2017) found university significantly influencing entrepreneurial intent among students. Indeed, Urbano and Guerrero (2013) suggested expanding the scope of university from traditional knowledge-generating to more of an enabler of entrepreneurial eco-system providing the concept of entrepreneurial university.…”
Section: Entrepreneurial Intention Among Studentsmentioning
confidence: 99%
“…Moreover, the effect of university environment to the entrepreneurial intention was higher than personality traits, attitudes, and socio-economic environmental factors. Zollo et al (2017) found that entrepreneurial intention of students is significantly affected by the university. It has also been identified by Kraaijenbrink et al (2009) andSaeed et al (2015) that there are three kinds of support a university can provide to its students, those are perceived educational support, perceived concept development support and perceived business development support, and they are important for the supportive university environment.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 98%